Impossibility of Performance in Environmental Contracts: A Case Study of the Merapi Volcano Eruption and Its Impact on Contractual Obligations - Admiral, Admiral; Adinda, Fadhel Arjuna; Hamzah , Rosyidi; Maisa, Maisa; Arifin, Ridwan (Universitas Negeri Semarang, 2025)
This paper examines the application of the doctrine of impossibility of performance in the context of environmental contracts in Indonesia, using the 2010 Merapi volcano eruption as a case study. The eruption, one of the most significant in recent decades, caused widespread destruction to infrastructure, agriculture, and local communities in Central Java. The paper investigates how businesses and government entities, bound by contractual obligations related to the affected regions—particularly in agriculture, tourism, and infrastructure—dealt with their inability to fulfill performance due to the eruption’s catastrophic consequences. Through an analysis of specific contracts and the invocation of force majeure and impossibility of performance clauses, this research seeks to understand how these legal doctrines were applied or misapplied, and whether they provided adequate relief or recourse for affected parties. The paper also explores the balance between contractual freedom and public interest in the face of natural disasters, considering the impact on long-term environmental recovery and business continuity. By analyzing case studies from key industries such as agriculture and tourism, the paper contributes to a deeper understanding of how environmental disasters challenge the enforcement of contractual obligations. It offers recommendations for adapting Indonesian contract law to better address environmental risks and unforeseen natural events, ensuring more robust protections for businesses and affected communities. This research contributes to the ongoing dialogue on improving the resilience of environmental contracts in the face of unpredictable natural phenomena.